2010
DOI: 10.1002/jnr.22527
|View full text |Cite
|
Sign up to set email alerts
|

The case for blood–brain barrier dysfunction in the pathogenesis of Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease that leads to a progressive loss of integrative and memory capacities of the brain. This is the predominant form of neurodegenerative dementia, with a growing prevalence of between 1 in 50 and 1 in 100 in North America. Numerous hypotheses related to the etiology of AD have developed over the years. However, among the various published hypotheses, the predominant one is related to the progressive and prominent accumulation of central nervous system β-amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 67 publications
3
30
0
Order By: Relevance
“…The physical, molecular, and transporter barrier properties of the BBB are each responsible for maintaining CNS homeostasis [1,45,52]. Histopathological analysis of various neurologic diseases have revealed that BBB dysregulation and breakdown is a common feature in many of these disorders, lending proof to the hypothesis that a functional BBB is required for a healthy CNS [2,6,49,[53][54][55][56][57]. Moreover, there is evidence that this works in the opposite direction as well; that a healthy CNS microenvironment is essential for maintaining the functional barrier properties of the BBB via cross-talk between neural cells and ECs [2].…”
Section: Features Of the Adult Bbbmentioning
confidence: 96%
“…The physical, molecular, and transporter barrier properties of the BBB are each responsible for maintaining CNS homeostasis [1,45,52]. Histopathological analysis of various neurologic diseases have revealed that BBB dysregulation and breakdown is a common feature in many of these disorders, lending proof to the hypothesis that a functional BBB is required for a healthy CNS [2,6,49,[53][54][55][56][57]. Moreover, there is evidence that this works in the opposite direction as well; that a healthy CNS microenvironment is essential for maintaining the functional barrier properties of the BBB via cross-talk between neural cells and ECs [2].…”
Section: Features Of the Adult Bbbmentioning
confidence: 96%
“…Though it was at one time suggested that AD/SDAT is a hippocampal dementia, the prevailing view is now that neocortical lesions are a necessary substrate of cognitive decline (158). Abnormalities of cerebral microcirculation (i.e., the neurovascular unit, which includes the capillary and arteriolar endothelium and surrounding pericytes, SMCs, and astrocytes) have been suggested as key elements in AD/SDAT pathogenesis (159)(160)(161). The role of the perivascular spaces (surrounding brain parenchymal vessels) in clearing brain parenchymal Aβ is discussed above, including with reference to the consequences of Aβ vaccination.…”
Section: Cerebrovascular Disease and Alzheimer's Disease/senile Demenmentioning
confidence: 99%
“…[3][4][5] Type 2 diabetes mellitus (T2DM) has been highlighted as a major risk factor for cognitive decline.…”
mentioning
confidence: 99%
“…2 Such BBB impairment is mainly caused by hypoxia/ischemia and inflammation. [3][4][5] Type 2 diabetes mellitus (T2DM) has been highlighted as a major risk factor for cognitive decline. 6 However, the mechanisms involved are not completely understood.…”
mentioning
confidence: 99%